What can we learn from conformational profiling of GPCRs? - Hébert, Terry (Henry Stewart Talks, 2020)
Biased signaling will have an impact in clinical medicine, Pharma is moving into using signaling signatures to capture information during drug discovery process, The information of signaling signatures can never be “complete”, Conformational profiling may offer a huge time savings rather than extending signaling signatures, Conformational profiling needs to be done in relevant cell, tissue and animal models